Development of the Diffusive Gradient in Thin Film (DGT) Method with CaO/Biochar Binding Agent from Eggshells and Rice Straw Waste for Determining the Concentration of Phosphate - Asep Saefumillah; Siti Zahara (Jurnal Kimia Sains dan Aplikasi, 2024)
Phosphorus, often found in the form of phosphate in the environment, especially aquatic environments, has been identified as the primary contaminant that causes algae blooms and eutrophication. Phosphate adsorption in the aquatic environment was carried out by comparing the adsorption capabilities of eggshell (CaO), rice straw (BC) and CaO/biochar materials at mass variations of 1:1, 1:2 and 2:1 from the use of eggshell and rice straw waste. Each material was synthesized using ball milling and pyrolysis methods. The adsorption isotherm and kinetics of the material are by the Langmuir adsorption isotherm and are pseudo-second-order (PSO) adsorption kinetics. The CaO/biochar 1:2 material shows the highest phosphate adsorption capacity at pH 12 with a contact time of 24 hours. CaO/biochar 1:2 was applied in the phosphate adsorption process using the Diffusive Gradient in Thin Film method as a binding agent, which acts as an adsorbent. The DGT technique is an in situ sample preparation technique for identifying the presence of phosphate, a labile species. The binding agent material was characterized using FTIR, XRD, and BJH-BET instruments. The success of synthesizing CaO/biochar 1:2 binding gel and ferrihydrite was demonstrated by the appearance of the same adsorption as the diffusive gel using FTIR. The CaO/biochar binding gel demonstrated that it is a better material compared to the ferrihydrite binding gel for phosphate adsorption, achieving CDGT values of 10.1727 mg/L and 2.5959 mg/L at pH 5 and 3, respectively, with a phosphate concentration of 10 mg/L. These findings underscore the potential of CaO/biochar as a more effective material for phosphate removal applications.